A comparison of soda lime (Intersurgical) with Amsorb® plus: the cost implications - Helmi AH,; Esa Kamaruzaman,; Khairulamir Zainuddin,; Azarinah Izaham,; Nurlia Yahya,; Nadia Md Nor, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
This was a prospective study comparing the cost implications between two carbon dioxide (CO2) absorbers, soda lime (Intersurgical) and AMSORB® PLUS. The study was conducted over two 4-week periods in two dedicated operating theatres using Datex Ohmeda Aestiva/5 anaesthetic machines. AMSORB® PLUS was used during the first four weeks and soda lime (Intersurgical) the following four weeks. General anaesthesia was administered as routinely done but fresh gas flow (FGF) during the maintenance phase was limited to a maximum flow of 2 L/min. The CO2 absorber was only changed when there was evidence of exhaustion. Total duration of anaesthesia, sevoflurane (bottles) and CO2 absorber (kg) consumption, and amount of waste product (kg) was calculated at the end of each study period. The total cost of delivering general anaesthesia was lower in the AMSORB® PLUS group, RM82.40 (USD19.89)/hour versus the soda lime group, RM91.50 (USD 22.09)/hour (p=0.17), which translates to a 10% reduction in cost per hour. Reduction in sevoflurane consumption in the AMSORB® PLUS compared to the soda lime group was also not statistically significant (p=0.22). The only significant finding was the reduction in CO2 absorber consumption in the AMSORB® PLUS group as compared to soda lime group (p=0.001). In conclusion, AMSORB® PLUS consumption was significantly reduced compared to that of soda lime. However, the use of AMSORB® PLUS did not significantly reduce sevoflurane consumption nor the total cost of delivering general anaesthesia. Given the superior safety profile, AMSORB® PLUS may be a suitable, cost-effective alternative to soda lime in the daily practice of anaesthesia.